RASAYANA: THE REJUVENATING REMEDY FOR HEALTH (International Journal of Ayurveda and Pharma Research, 2018)
Gradual increase of Population in urban area may leads to environmental pollution and microbial infection in air and water increases exponentially. Most of the persons in the population are in trap of mental stress and depression due to struggle in the life and overload of work. So both of these conditions are responsible for so many disease and ill-health, and one more important thing is that due to increase negligence and uninhabited use of processed food, the ill effects on health are compound manifold when coupled with unhealthy lifestyle and food habits. So there is a need of taking dietary supplementary food or nutraceutical. The main aim of Ayurveda has been working upon a twofold process i.e., to maintain the health of a healthy individual and to treat the one with the disease. Thus by laying emphasis on the first aspect and combining it with the knowledge of the role of phytochemical as, one can gradually deduce an effective module for living healthy and line of treatment of metabolic and geriatric disorders. The phytochemical are the essential nutrients, which are naturally contained in plants and are required for normal physiological functions. The Rasayan not only boost general health but also provide the necessary raw materials to strengthen the defense mechanism of the body.